Penerapan Perawatan Payudara (Breast Care) Terhadap Pembengkakan Payudara Pada Ibu Menyusui Post Partum Di Bangsal Cempaka RSUD dr. Soehadi Prijonegoro Sragen - Khisan Fajri Nur Khasanah; Maryatun Maryatun; Neny Utami (Stikes Kesdam IV/Diponegoro Semarang, Indonesia, 2023)
Breastfeeding-related problems such as breast milk dams, mastitis, nipple blisters and others are widely experienced by breastfeeding mothers. Factors that can cause breast swelling and inhibition of ASi, one of which is the feeling of anxiety or stress felt by postpartum mothers. Breast care has tremendous benefits, especially for postpartum mothers in the process of breastfeeding their babies. The benefits of breast care are that mothers understand how to keep breasts clean, make nipples stronger and flexible, care for flat or inverted nipples, and facilitate the release of breast milk. To find out the results of breast care implementation in the cempaka ward of RSUD dr. Soehadi Prijonegoro Sragen. This study used quasi-experiment, one group with pretest-posttes Without Control Group Design with 2 respondents postpartum mothers. The instrument used is a Checklist containing six-point engorgement scale (SPES) and Breast Care Procedure.: the results of the application of breast care carried out 3 days in a row obtained the value of the Six Point Engorgement Scale questionnaire there was a decrease in scores, namely 2 and 1 from the original values of 5 and 4 which means there was a decrease in breast swelling. there was a significant difference in the Six Point Engorgement Scale (SPES) score in postpartum maternal patients between before and after breast care every 30 minutes for 3 days.